2009
DOI: 10.5012/bkcs.2009.30.11.2613
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction of FeOOH and TiO2for the Formation of Visible Light Photocatalyst

Abstract: FeOOH/TiO2, a heterojunction structure between FeOOH and TiO2, was prepared by covering the surface of the ~100-nm-sized FeOOH particles with Degussa P25 by applying maleic acid as an organic linker. Under visible light irradiation (λ ≥ 420 nm), FeOOH/TiO2 showed a notable photocatalytic activity in removal of gaseous 2-propanol and evolution of CO2. It was found that FeOOH reveals a profound absorption in the spectral range of 400 -550 nm, and its valence band (VB) level is located relatively lower than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Iron oxide hydroxide (FeOOH) has been utilized as a starting precursor to produce £-Fe 2 O 3 and ¡-Fe 2 O 3 by performing thermal annealing at different temperatures. 17) Additionally, £-FeOOH material has exhibited promising effects as a photocatalyst combined with TiO 2 18) and adsorbent materials for removal of heavy ions. 19) Recently, we reported the n-type semiconductor properties of £-FeOOH thin films electrodeposited from oxygenbubbled aqueous solutions at room temperature.…”
mentioning
confidence: 99%
“…Iron oxide hydroxide (FeOOH) has been utilized as a starting precursor to produce £-Fe 2 O 3 and ¡-Fe 2 O 3 by performing thermal annealing at different temperatures. 17) Additionally, £-FeOOH material has exhibited promising effects as a photocatalyst combined with TiO 2 18) and adsorbent materials for removal of heavy ions. 19) Recently, we reported the n-type semiconductor properties of £-FeOOH thin films electrodeposited from oxygenbubbled aqueous solutions at room temperature.…”
mentioning
confidence: 99%
“…For example, Li et al very recently demonstrated that deposited Ag 3 PO 4 nanoparticles on (040) facets of large BiVO 4 crystals could efficiently degrade methylene blue (MB), how the CB of BiVO 4 lies at a more positive position than the CB of Ag 3 PO 4 and reasons of its excellent stability[56]. Very recently, FeOOH was shown to have favorable conduction band positioning (+0.5 V Vs. NHE) and also shown to have significant enhancement in the photooxidation ability of BiVO 4 when deposited as a catalyst, boosting IPCE (incident photon-to-electron conversion) from 9% up to 60% in the visible light range[57][58]. Considering the position of the CB of Ag 3 PO 4 (Ca.…”
mentioning
confidence: 99%